Notice of Bronze Relics, &c., found in the Isle of Skye (Proceedings of the Society of Antiquaries of Scotland, 1862)
John Alex Smith displayed some illustrations of bronze artefacts found in a peat bog on the Isle of Skye. He notes their similarity to other bronze finds from Scotland but is unable to accurately date them. He also comments on some of the personal artefacts that were once owned by Flora MacDonald, now in the possession of Lord and Lady MacDonald. Meeting notes for 12 April, 1858 are appended.